2001
DOI: 10.1254/jjp.85.313
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Heart Rate Are Increased by AF-DX 116, a Selective M2 Antagonist, in Autonomic Imbalanced and Hypotensive Rats Caused by Repeated Cold Stress

Abstract: ABSTRACT-Rats exposed to SART (specific alternation of rhythm in temperature) stress, which are ideal animal models for vagotonia-type dysautonomia, show various changes in cardiac and circulatory systems. In this study, attention was directed to cholinergic function in the SART-stressed rat heart and the effects of AF-DX 116, a specific muscarinic M 2 antagonist, on blood pressure and heart rate. The results were compared with those obtained for atropine and pirenzepine. In SART-stressed rats, systolic and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…In the manifestation of severe OH in SARTstressed rats, in particular, along with the already reported association with vagus nerve and M 2 -receptors, 18) changes in sympathetic stimulation to the heart, changes in the sensitivity of b 1 -adrenoceptors in heart and changes in b 2 -adrenoceptors in peripheral blood vessels seem to play roles. In other words, the balance of the autonomic nervous system seems to function poorly in the nervous reflex in head up tilting in SART-stressed rats.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…In the manifestation of severe OH in SARTstressed rats, in particular, along with the already reported association with vagus nerve and M 2 -receptors, 18) changes in sympathetic stimulation to the heart, changes in the sensitivity of b 1 -adrenoceptors in heart and changes in b 2 -adrenoceptors in peripheral blood vessels seem to play roles. In other words, the balance of the autonomic nervous system seems to function poorly in the nervous reflex in head up tilting in SART-stressed rats.…”
Section: Discussionsupporting
confidence: 61%
“…Basic items had the similar results as in the previous reports. 1,2,15,18,19) Effects of drugs are summarized in Fig. 7 for the discussion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, our recent studies found that the SART-stressed rats had marked OH, suggesting the rats could be an OH model animal (9). In order to elucidate the mechanism of OH, we investigated the effect of AF-DX116, a selective muscarinic M 2 -receptor antagonist, which has been observed to remarkably improve hypotension in SART-stressed rats (10). Effects of other muscarinic receptor antagonists were investigated and compared with that of AF-DX116.…”
Section: Introductionmentioning
confidence: 99%